I'm not sure if: Is the complete problem. Can you double check it?
yeah its supposed to simplify to sec^2(x)
To solve this question, you need to trigonometry identity: (1) cos2(x) + sin2(x) = 1 (2) tan2(x) + 1 = sec2(x) By using (1), you will realise 1-sin2(x) = cos2(x), so the fraction cancels itself! 1-sin2(x)/cos2(x) = cos2(x)/cos2(x) = 1 Then you are left with: 1+tan2(x) Which is sec2(x) because of (2) Note that (2) can be derived from (1) by dividing the whole equation by cos2(x) cos2(x)/cos2(x) +sin2(x)/cos2(x) = 1/cos2(x) 1+tan2(x) = sec2(x)
Add an answer